Method for synthesizing nanosheet ZSM-23 zeolite molecular sieve by using biquaternary ammonium base organic template agent

The synthesis of nanosheet-like ZSM-23 zeolite molecular sieves using bis-quaternary ammonium base organic template agents solves the problem of limited catalytic performance caused by pore structure in existing technologies, achieving higher catalytic activity and mass transfer efficiency, and is suitable for long-chain alkane isomerization reactions.

CN121318831APending Publication Date: 2026-01-13ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511348185.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-20
Publication Date
2026-01-13

AI Technical Summary

Technical Problem

The pore structure of existing ZSM-23 zeolite molecular sieves limits their catalytic performance, making it difficult to exhibit high catalytic efficiency in hydrocarbon isomerization reactions, especially due to the increased product diffusion resistance caused by the longer pore orientation.

Method used

Using a dual-quaternary ammonium base organic template agent, and through specific molecular structure design, a rigid benzene ring is used to determine the pore framework and a flexible pyrrolidine ring is used to adapt to the zeolite framework. Combined with space filling, dynamic orientation control, nucleation size control and charge balance control, nanosheet-like ZSM-23 zeolite molecular sieves are synthesized.

Benefits of technology

The synthesized nanosheet-like ZSM-23 zeolite molecular sieve exhibits higher catalytic activity and mass transfer efficiency, improving alkane conversion and single isomer selectivity, and is suitable for long-chain alkane isomerization reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121318831A_ABST
    Figure CN121318831A_ABST
Patent Text Reader

Abstract

The invention relates to a molecular sieve morphology regulation and control preparation technology, and aims to provide a method for synthesizing a nanosheet ZSM-23 zeolite molecular sieve by using a double quaternary ammonium base organic template agent. Comprising the following steps: mixing water, a silicon source, an aluminum source, an alkali source and a biquaternary ammonium base organic template agent solution which are used as reaction raw materials, and uniformly stirring to obtain a gel mixture; transferring the gelatinous mixture into a reaction kettle for dynamic crystallization reaction, and centrifuging, washing and drying a reaction product to obtain the zeolite molecular sieve. The molecular structural formula of the bis-quaternary ammonium base organic template agent is shown as a formula I in the specification. According to the invention, the rigid framework is utilized to determine the structure and the flexible tail end adapts to and stabilizes the characteristics of the structure, so that the template agent with higher guiding efficiency is obtained; the molecular sieve synthesized by a hydrothermal single-template method is of a nanoscale sheet structure, has higher alkane conversion rate, monoisomer selectivity and yield, shows better mass transfer efficiency, and is very suitable for long-chain alkane isomerization reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention pertains to methods for preparing molecular sieves by regulating their morphology, and specifically relates to a method for synthesizing ZSM-23 zeolite nanosheets using a bisquaternary ammonium base organic template agent. Background Technology

[0002] ZSM-23 zeolite molecular sieve is a mesoporous, high-silica zeolite with an MTT topology, in which the one-dimensional channels are composed of teardrop-shaped ten-membered rings with a free diameter of 0.52 × 0.45 nm. It was first synthesized in 1978 by Plank et al. of Mobil Corporation in the United States. Due to its unique shape selectivity, it has wide applications in fields such as hydroisomerization and methanol-to-olefins (MTO). Its channel structure effectively inhibits the formation of aromatics, enabling highly selective production of C3-C6 olefins in methanol-to-olefins reactions. In the isomerization of long-chain alkanes, it improves the low-temperature fluidity of lubricating oils, significantly enhancing oil quality.

[0003] In the synthesis of ZSM-23 zeolite molecular sieves, template agents play a crucial role as structure-directing agents. In early studies, pyrrolidine was the first template agent used, but it tended to form large, plate-like or date-shaped crystals, leading to reduced mass transfer efficiency through the pores. Subsequent studies developed several superior template agent systems. For example, isopropylamine (IPA) can synthesize rod-shaped ZSM-23 zeolite molecular sieves with a crystal cross-sectional diameter of approximately 75 nm, and can be tuned to produce short-axis nanorods with a small aspect ratio, significantly increasing the external specific surface area; alternatively, a mixed template agent of dimethylamine and pyrrolidine can be used. Furthermore, small-molecule organic amines such as n-butylamine, ethylenediamine, and diisobutylamine have also been proven to be effective template agents, and ZSM-23 zeolite molecular sieves synthesized using these template agents often exhibit a rod-shaped structure.

[0004] In summary, ZSM-23 zeolite molecular sieves prepared using existing template agents are needle- or rod-shaped crystals with a one-dimensional channel structure. The channels are oriented along the long axis, while the pores are arranged along the crystal interface or radial direction. However, it is well known that the activity of hydrocarbon isomerization reactions is mainly affected by the pore size limitation and diffusion of the catalyst support. The relatively long channel orientation in ZSM-23 zeolite molecular sieves increases the diffusion resistance of the products, reducing their catalytic performance. Therefore, developing nanoscale, plate-like ZSM-23 zeolite molecular sieves with more surface active centers and shorter mass transport pathways to improve their catalytic performance in hydrocarbon isomerization reactions would be of great industrial significance. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for synthesizing nanosheet ZSM-23 zeolite molecular sieves using a bis-quaternary ammonium base organic template agent.

[0006] To solve the technical problem, the solution of the present invention is:

[0007] First, a method for preparing a bisquaternary ammonium base organic template agent is provided, including:

[0008] (1) Weigh p-dibromobenzyl and 4-pyrrolidinylpyridine in a molar ratio of 1:2 to 5, and then add them to an appropriate amount of acetonitrile; heat and reflux at 50 to 100 °C for 1 to 4 days;

[0009] (2) After the reaction is complete, add sufficient diethyl ether to the system to form a white solid precipitate; after filtration and drying, obtain bisquaternary ammonium bromide powder;

[0010] (3) Dissolve an appropriate amount of quaternary ammonium bromide powder in water, and perform exchange treatment with a hydroxide-type anion exchange resin to remove impurity anions and introduce a quantitative amount of OH. - A solution containing a bisquaternary ammonium base organic template agent R was obtained;

[0011] The molecular structure of the bisquaternary ammonium base organic template agent R is shown in Formula I below:

[0012] (Formula I).

[0013] As a preferred embodiment of the present invention, in step (1), the molar ratio of acetonitrile to p-dibromobenzyl is 1:30 to 80.

[0014] As a preferred embodiment of the present invention, in step (3), the anion exchange resin is added to a bisquaternary ammonium bromide aqueous solution and stirred at room temperature for more than 24 hours; then, 0.1 mol / L hydrochloric acid solution is added to remove OH- ions from the solution. - Quantitative calibration was performed to achieve a concentration of 1–2 mmol / g.

[0015] As a preferred embodiment of the present invention, the hydroxyl-type anion exchange resin is Amberlite® IRN-78.

[0016] Furthermore, this invention also provides a method for further synthesizing nanosheet-like ZSM-23 zeolite molecular sieves using the aforementioned bis-quaternary ammonium base organic template agent, comprising the following steps:

[0017] (1) Weigh the water, silicon source, aluminum source, alkali source and bisquaternary ammonium base organic template agent solution as reaction raw materials, in a molar ratio of 15-40 H2O:SiO2:0-0.02 Al2O3:0.02-0.08 (Na2O or K2O):0.1-0.5 template agent R; mix the raw materials and stir until uniform to obtain a gel-like mixture;

[0018] (2) Transfer the gel-like mixture to a reaction vessel and allow it to undergo dynamic crystallization reaction at 120–180 °C for 3–7 days;

[0019] (3) The reaction product was centrifuged, washed and dried to obtain nanosheet ZSM-23 zeolite molecular sieve.

[0020] As a preferred embodiment of the present invention, the water is deionized water; the silicon source is fine silica gel (100% SiO2), white carbon black (100% SiO2), or silica sol (40% SiO2) with a solid content of 40%; the aluminum source is aluminum sulfate octadechydrate, aluminum nitrate nonahydrate, or sodium aluminate; and the alkali source is potassium hydroxide or sodium hydroxide.

[0021] Description of the invention principle:

[0022] 1. The innovation of this invention lies in the use of a novel bis-quaternary ammonium base with a specific molecular structure as an organic template agent for the preparation of ZSM-23 zeolite nanosheets. In the molecular structure of this bis-quaternary ammonium base, the rigid benzene ring structure is mainly responsible for defining the overall framework of the channels. The flexible pyrrolidine onlonium ring at the ends can better fit with the growing, not perfectly regular, zeolite framework surface through certain rotational and conformational adjustments, and provide additional stabilization through non-covalent interactions such as van der Waals forces. This characteristic of "using a rigid framework to define the structure and using flexible ends to adapt to and stabilize the structure" makes the template agent highly efficient in guiding. Therefore, compared with the three most commonly used organic template agents on the market—N,N-dimethylformamide, pyrrolidine, and Triquat-7—the novel bis-quaternary ammonium base provided by this invention has lower stabilization energy and superior guiding performance when guiding ZSM-23 zeolite molecular sieves. On the other hand, theoretical calculations show that when these three known organic templates are used for molecular sieve synthesis, the surface energy of the

[100] crystal plane is significantly lower than that of the

[010] and

[001] crystal planes. This means that ZSM-23 zeolite molecular sieves tend to grow into rod-shaped morphology along the

[100] direction rather than the sheet-like structure expected in this invention.

[0023] 2. Unlike existing template agents, the introduction of the novel quaternary ammonium base of this invention into the synthesis system of ZSM-23 zeolite molecular sieve results in an increased surface energy of the

[100] crystal facet and a decreased surface energy of the

[010] and

[001] crystal faces. Furthermore, during the generation of ZSM-23 zeolite molecular sieve, the surface energies of the

[001] and

[100] crystal faces are lower than those of the

[010] surface. This difference in surface energy leads to different crystal growth trends, thereby promoting the nanosheet morphology along the a-axis and c-axis. This specific morphology of ZSM-23 zeolite nanosheets has more surface active centers and shorter mass transport pathways, exhibiting better catalytic performance compared to needle-shaped or rod-shaped zeolites prepared using traditional template agents.

[0024] 3. Considering the molecular geometry and pore matching of the template agent, the rigid benzene ring framework of the novel quaternary ammonium base in this invention is highly compatible with the spatial dimension of the one-dimensional pores of ZSM-23 zeolite molecular sieve. Its two quaternary ammonium cations are connected to the benzene ring through methylene groups, forming a structure similar to a "double anchor," and guide the growth of ZSM-23 zeolite molecular sieve crystals through the following multiple mechanisms:

[0025] (1) Space filling effect: The benzene ring occupies the cross-section of the pores laterally, inhibiting the formation of cross-channel structures such as ZSM-5;

[0026] (2) Dynamic orientation regulation: The flexible chain of pyrrolidinyl allows the molecule to adaptively adjust its conformation during crystallization, precisely matching the sinusoidal channel bending angle of the MTT structure; the secondary amine hydrogen in the pyrrolidinyl can form hydrogen bonds with the silanol group, promoting the local ordering of the aluminosilicate precursor. This hydrogen bond network is particularly crucial in the early stage of crystallization, as it can reduce the nucleation energy barrier and increase the nucleus density by more than 30%;

[0027] (3) Nucleation size control: Due to the strong guiding ability of the quaternary ammonium salt template agent, the molecular size of the template agent and the critical size of the MTT channel form a "size sieving" effect, which preferentially inhibits the nucleation of non-target structures; it can increase the crystallinity of ZSM-23 zeolite molecular sieve to more than 95%, and the impurity content is less than 2%;

[0028] (4) Charge balance regulation: During crystallization, the quaternary ammonium cations of the bis-quaternary ammonium base can be selectively adsorbed onto specific crystal faces, guiding aluminum atoms to preferentially enter specific positions on the pore wall to achieve charge balance. In the characterization of acid sites, the Brønsted acid density of ZSM-23 zeolite molecular sieve synthesized using bis-quaternary ammonium salt is 30% higher than that of traditional template agents, and the acid site distribution is more uniform, which is beneficial to the selective improvement of reactions such as long-chain alkane isomerization.

[0029] (5) Maintaining structural stability: The presence of the aromatic ring (pyridine, benzene) of the novel quaternary ammonium base endows the molecule with high thermal stability, enabling it to withstand the hydrothermal conditions required for the synthesis of ZSM-23, maintain structural integrity throughout the crystallization process, and continuously play the role of template.

[0030] Compared with the prior art, the beneficial effects of the present invention are:

[0031] 1. This invention utilizes a novel quaternary ammonium base organic template agent to synthesize ZSM-23 zeolite molecular sieves via a hydrothermal single-template method. The product exhibits a nanoscale sheet-like structure with a thickness of 10-15 nm. This design not only broadens the types of organic template agents for synthesizing ZSM-23 zeolite molecular sieves but also enables the synthesis of nanosheet-like morphologies that differ from conventional ZSM-23 zeolite molecular sieves.

[0032] 2. Compared with existing technologies, this invention only requires the use of one organic template agent in the entire production process, and the obtained product maintains good crystallinity and purity, with a yield of up to 95% and good catalytic activity. Therefore, this invention is of great significance in the field of practical chemical production.

[0033] 3. The ZSM-23 zeolite nanosheets prepared using the organic template agent of this invention have higher alkane conversion rate, monoisomeric selectivity and yield compared with conventional rod-shaped and date-shaped ZSM-23 zeolite molecular sieves, thus demonstrating that the nanosheet structure has better mass transfer efficiency than conventional ZSM-23 zeolite molecular sieves.

[0034] 4. The bis-quaternary ammonium base template agent in this invention significantly improves the synthesis efficiency and performance of ZSM-23 zeolite molecular sieves through synergistic mechanisms such as the spatial guidance of the rigid benzene ring, the charge balance of the bis-quaternary ammonium cations, and the flexible adjustment of the pyrroleyl group. Its functional group characteristics not only solve the bottlenecks of traditional template agents in terms of crystallinity, impurity crystal control, and acidity regulation, but also provide a new strategy for the large-scale application of ZSM-23 zeolite molecular sieves in the refining, chemical, and environmental fields. In the future, further optimization of intramolecular interactions through functional group engineering is expected to develop more efficient zeolite synthesis systems.

[0035] 5. In the bisquaternary ammonium base of this invention, the secondary amine hydrogen (-NH-) of the pyrroleyl group forms a hydrogen bond network with the silanol group (Si-OH), which promotes the uniform distribution of acid sites and can suppress the cracking side reaction of ZSM-23 zeolite molecular sieve in the hydroisomerization reaction; and the five-membered ring structure of the pyrroleyl group allows the molecule to adjust its orientation during crystallization, precisely matching the pore structure of ZSM-23 zeolite molecular sieve, thereby reducing the mass transfer resistance of reactants in the hydroisomerization reaction and improving the reaction performance.

[0036] 6. In the process of preparing the quaternary ammonium base organic template agent solution, the present invention utilizes hydroxyl-type anion exchange resin to activate the template agent, remove impurities, regulate alkalinity, and simplify post-processing. This is a key step that ensures the quality of zeolite molecular sieve synthesis from the core level and directly determines the topology, framework integrity, pore performance, and subsequent application (such as catalysis and adsorption) of the molecular sieve.

[0037] 7. Zeolite molecular sieves with different topologies and channels correspond to different industrial catalytic application scenarios. The zeolite molecular sieve prepared by the present invention based on a novel quaternary ammonium base organic template agent is very suitable for long-chain alkane isomerization reaction.

[0038] As a significant difference, consider this application scenario: Because ZSM-23 zeolite molecular sieves have one-dimensional ten-membered ring channels (pore size 0.45~0.52 nm), while lactide is a six-membered ring molecule with a molecular dynamic diameter of approximately 0.6~0.7 nm, lactide cannot effectively diffuse out of the ZSM-23 zeolite molecular sieve channels, accumulating within the channels and reacting. Therefore, the ZSM-23 zeolite molecular sieve of this invention cannot be used in the lactic acid to lactide reaction. Furthermore, the acidic sites of ZSM-23 zeolite molecular sieves are characterized by a high proportion of strong acid centers and concentrated acid density, which conflicts with the requirement for moderately strong, dispersed acid sites in the lactic acid to lactide reaction. Consequently, the strong acid sites of ZSM-23 zeolite molecular sieves can lead to over-catalysis and the generation of numerous byproducts. Therefore, ZSM-23 zeolite molecular sieves, due to their excessively narrow and easily clogged micropores and mismatched strong acidity, are completely unsuitable for the lactic acid to lactide reaction.

[0039] However, the situation is completely different when taking the hydroisomerization reaction of n-hexadecane as an example. The n-hexadecane molecule begins at one end of the carbon chain, with segments of four consecutive carbon atoms inserted into the pores. In the nanosheet-like ZSM-23 zeolite molecular sieve prepared by this invention using a bis-quaternary ammonium base organic template agent, the one-dimensional ten-membered ring channel (0.45 × 0.52 nm) forms a lock-and-key match with the molecular dynamic diameter of n-hexadecane (approximately 0.4~0.5 nm). Simultaneously, the acidic sites of the nanosheet-like ZSM-23 zeolite molecular sieve exhibit moderate strength, pore enrichment, and tunability, which highly aligns with the requirements of the hydroisomerization reaction. Therefore, the ZSM-23 zeolite molecular sieve of this invention, with its precisely matched pore structure, moderately strong acidic sites, excellent thermal stability, and tunable surface properties, becomes an ideal catalyst for the isomerization reaction of long-chain alkanes. Attached Figure Description

[0040] Figure 1 The XRD pattern of ZSM-23 zeolite nanosheets synthesized using a novel quaternary ammonium base organic template agent.

[0041] Figure 2 This is a scanning electron microscope image (low magnification) of the ZSM-23 zeolite nanosheets in this invention.

[0042] Figure 3 This is a scanning electron microscope (SEM) image (high magnification) of the ZSM-23 zeolite nanosheets used in this invention.

[0043] Figure 4 This is a transmission electron microscope (TEM) image of the ZSM-23 zeolite nanosheets used in this invention.

[0044] Figure 5 The XRD pattern of ZSM-23 zeolite molecular sieve synthesized using N,N-dimethylformamide.

[0045] Figure 6 Scanning electron microscope image of ZSM-23 zeolite molecular sieve synthesized using N,N-dimethylformamide.

[0046] Figure 7 The XRD pattern of ZSM-23 zeolite molecular sieve synthesized using pyrrolidine.

[0047] Figure 8 Scanning electron microscope image of ZSM-23 zeolite molecular sieve synthesized using pyrrolidine.

[0048] Figure 9 The XRD pattern of ZSM-23 zeolite molecular sieve synthesized using Triquat-7.

[0049] Figure 10 Scanning electron microscope image of ZSM-23 zeolite molecular sieve synthesized using Triquat-7. Detailed Implementation

[0050] I. Overview of the Technical Solution of the Invention

[0051] First, this invention proposes a method for preparing a novel quaternary ammonium base organic template agent, comprising:

[0052] (1) Weigh p-dibromobenzyl, 4-pyrrolidinylpyridine and acetonitrile in a molar ratio of 1:2 to 5:30 to 80, and add the two solid powders to acetonitrile as a solvent in sequence; heat and reflux at 50 to 100 °C for 1 to 4 days;

[0053] (2) After the reaction is complete, add sufficient diethyl ether to the system to form a white solid precipitate; after filtration and drying, obtain bisquaternary ammonium bromide powder;

[0054] (3) Dissolve an appropriate amount of quaternary ammonium bromide powder in water, add the hydroxide-type anion exchange resin to the quaternary ammonium bromide aqueous solution, and stir at room temperature for more than 24 hours to carry out exchange treatment, remove impurity anions and introduce OH. - Using 0.1 mol / L hydrochloric acid solution to treat OH- - Quantitative calibration was performed to make OH - A solution of the bisquaternary ammonium base organic template agent R was obtained at a concentration of 1–2 mmol / g; the molecular structure of the bisquaternary ammonium base organic template agent R in this solution is shown in Formula I below:

[0055] (Formula I).

[0056] As an example, the hydroxyl-type anion exchange resin model can be Amberlite® IRN-78.

[0057] This invention further proposes a method for synthesizing nanosheet-like ZSM-23 zeolite molecular sieves using this bisquaternary ammonium base organic template agent, comprising the following steps:

[0058] (1) Weigh the water, silicon source, aluminum source, alkali source and bisquaternary ammonium base organic template agent solution as reaction raw materials, in a molar ratio of 15-40 H2O:SiO2:0-0.02 Al2O3:0.02-0.08 (Na2O or K2O):0.1-0.5 template agent R; mix the raw materials and stir until uniform to obtain a gel-like mixture;

[0059] (2) Transfer the gel-like mixture to a reaction vessel and allow it to undergo dynamic crystallization reaction at 120–180 °C for 3–7 days;

[0060] (3) The reaction product was centrifuged, washed and dried to obtain nanosheet ZSM-23 zeolite molecular sieve.

[0061] As an optional example, the water is deionized water; the silicon source is fine silica gel (100% SiO2), fumed silica (100% SiO2), or silica sol (40% SiO2) with a solid content (mass percentage) of 40%; the aluminum source is aluminum sulfate octadechydrate, aluminum nitrate nonahydrate, or sodium aluminate; and the alkali source is potassium hydroxide or sodium hydroxide.

[0062] II. Examples and Comparative Examples

[0063] Example 1: Synthesis of a novel bisquaternary ammonium base organic template agent

[0064] 246 g of acetonitrile was added to 52.8 g of p-dibromobenzyl, followed by 59.3 g of 4-pyrrolidinylpyridine. The mixture was stirred and refluxed in an oil bath at 80 °C for 2 days. After the reaction was complete, sufficient diethyl ether was added to the reaction product. The resulting white solid precipitate was filtered and dried to obtain a bisquaternary ammonium bromide powder. The powder was then dissolved in water, exchanged with a hydroxide-type anion exchange resin, and quantitatively standardized to obtain OH... - A 1.00 mmol / g solution of bisquaternary ammonium base organic template agent R1.

[0065] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0066] p-Dibromobenzyl: 4-pyrrolylpyridine: acetonitrile = 1:2:30

[0067] Example 2: Synthesis of a novel bisquaternary ammonium base organic template agent under the condition of 4-pyrrolylpyridine / p-dibromobenzyl = 3.

[0068] 246 g of acetonitrile was added to 52.8 g of p-dibromobenzyl, followed by 88.9 g of 4-pyrrolidinylpyridine. The mixture was stirred and refluxed in an oil bath at 80 °C for 2 days. After the reaction was complete, sufficient diethyl ether was added to the reaction product. The resulting white solid precipitate was filtered and dried to obtain a bisquaternary ammonium bromide powder. The powder was then dissolved in water, exchanged with a hydroxide-type anion exchange resin, and quantitatively standardized to obtain OH. - A 1.20 mmol / g solution of bisquaternary ammonium base organic template agent R2.

[0069] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0070] p-Dibromobenzyl: 4-pyrrolylpyridine: acetonitrile = 1:3:30

[0071] Example 3: Synthesis of a novel bisquaternary ammonium base organic template agent under the condition of 4-pyrrolidinylpyridine / p-dibromobenzyl = 5.

[0072] 246 g of acetonitrile was added to 52.8 g of p-dibromobenzyl, followed by 148.2 g of 4-pyrrolidinylpyridine. The mixture was stirred and refluxed in an oil bath at 80 °C for 2 days. After the reaction was complete, sufficient diethyl ether was added to the reaction product. The resulting white solid precipitate was filtered and dried to obtain a bisquaternary ammonium bromide powder. The powder was then dissolved in water, exchanged with a hydroxide-type anion exchange resin, and quantitatively standardized to obtain OH. - A 1.43 mmol / g solution of bisquaternary ammonium base organic template agent R3.

[0073] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0074] p-Dibromobenzyl: 4-pyrrolylpyridine: acetonitrile = 1:5:30

[0075] Example 4: Synthesis of a novel bisquaternary ammonium base organic template agent under the condition of acetonitrile / p-dibromobenzyl = 80.

[0076] 656 g of acetonitrile was added to 52.8 g of p-dibromobenzyl, followed by 88.9 g of 4-pyrrolidinylpyridine. The mixture was stirred and refluxed in an oil bath at 80 °C for 2 days. After the reaction was complete, sufficient diethyl ether was added to the reaction product. The resulting white solid precipitate was filtered and dried to obtain a bisquaternary ammonium bromide powder. The powder was then dissolved in water, exchanged with a hydroxide-type anion exchange resin, and quantitatively standardized to obtain OH. - A 1.60 mmol / g solution of bisquaternary ammonium base organic template agent R4.

[0077] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0078] p-Dibromobenzyl: 4-pyrrolylpyridine: acetonitrile = 1:3:80

[0079] Example 5: Synthesis of a novel bisquaternary ammonium base organic template agent at a heating temperature of 50 °C

[0080] 410 g of acetonitrile was added to 52.8 g of p-dibromobenzyl, followed by 88.9 g of 4-pyrrolidinylpyridine. The mixture was stirred and refluxed in an oil bath at 50 °C for 4 days. After the reaction was complete, sufficient diethyl ether was added to the reaction product. The resulting white solid precipitate was filtered and dried to obtain a bisquaternary ammonium bromide powder. The powder was then dissolved in water, exchanged with a hydroxide-type anion exchange resin, and quantitatively standardized to obtain OH. - A 1.80 mmol / g solution of bisquaternary ammonium base organic template agent R5.

[0081] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0082] p-Dibromobenzyl: 4-pyrrolylpyridine: acetonitrile = 1:3:50

[0083] Example 6: Synthesis of a novel bisquaternary ammonium base organic template agent at a heating temperature of 100 °C

[0084] 410 g of acetonitrile was added to 52.8 g of p-dibromobenzyl, followed by 88.9 g of 4-pyrrolidinylpyridine. The mixture was stirred and refluxed in an oil bath at 100 °C for 1 day. After the reaction was complete, sufficient diethyl ether was added to the reaction product. The resulting white solid precipitate was filtered and dried to obtain a bisquaternary ammonium bromide powder. The powder was then dissolved in water, exchanged with a hydroxide-type anion exchange resin, and quantitatively standardized to obtain OH. - A 2.00 mmol / g solution of bisquaternary ammonium base organic template agent R6.

[0085] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0086] p-Dibromobenzyl: 4-pyrrolylpyridine: acetonitrile = 1:3:50

[0087] Example 7: Synthesis of ZSM-23 zeolite nanosheets using a novel quaternary ammonium base organic template agent

[0088] 6.667 g of the quaternary ammonium base R1 solution from Example 1, 0.780 g of water, and 0.111 g of aluminum sulfate octadecahydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.08 g of potassium hydroxide was added, followed by 2.5 g of silica sol (40% SiO2) under stirring. After stirring for another 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 150 °C for 5 days until complete crystallization. The product was centrifuged, washed, and dried to obtain ZSM-23 zeolite nanosheets.

[0089] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0090] 0.04 K2O: 1.0 SiO2: 0.01 Al2O3: 25 H2O: 0.20 R

[0091] X-ray diffraction analysis revealed its structure to be ZSM-23 zeolite molecular sieve (see...). Figure 1 ). Figure 2-3 The image shows a scanning electron microscope (SEM) image of ZSM-23 zeolite nanosheets. It can be seen that the synthesized zeolite product is in the form of thin sheets (low magnification), and the thickness of the sheets is less than 20 nm (high magnification). Figure 4 This is a transmission electron microscope (TEM) image of the zeolite product. The TEM image shows that the nanosheets are approximately 10–15 nm thick.

[0092] Example 8: Synthesis of ZSM-23 zeolite nanosheets under R / SiO2=0.1 conditions

[0093] 3.333 g of the quaternary ammonium base R1 solution from Example 1, 3.390 g of water, and 0.111 g of aluminum sulfate octadecahydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.08 g of potassium hydroxide was added, followed by 2.5 g of silica sol (40% SiO2) under stirring. After stirring for 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 150 °C for 5 days until complete crystallization. The product was centrifuged, washed, and dried to obtain ZSM-23 zeolite nanosheets.

[0094] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0095] 0.04 K2O: 1.0 SiO2: 0.01 Al2O3: 25 H2O: 0.10 R

[0096] Example 9: Synthesis of ZSM-23 zeolite nanosheets under R / SiO2=0.5 conditions

[0097] 8.333 g of the quaternary ammonium base R6 solution from Example 6, 3.384 g of water, and 0.111 g of aluminum sulfate octadecahydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.08 g of potassium hydroxide was added, followed by 2.5 g of silica sol (40% SiO2) under stirring. After stirring for another 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 150 °C for 5 days until complete crystallization. The product was centrifuged, washed, and dried to obtain ZSM-23 zeolite nanosheets.

[0098] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0099] 0.04 K2O: 1.0 SiO2: 0.01 Al2O3: 32 H2O: 0.50 R

[0100] Example 10: Synthesis of ZSM-23 zeolite nanosheets at a crystallization temperature of 120℃

[0101] 5.556 g of the quaternary ammonium base R2 solution from Example 2, 1.891 g of water and 0.111 g of aluminum sulfate octadecahydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.08 g of potassium hydroxide was added, followed by 2.5 g of silica sol (40% SiO2) under stirring. After stirring for 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 120°C for 7 days until complete crystallization. The product was centrifuged, washed and dried to obtain ZSM-23 zeolite nanosheets.

[0102] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0103] 0.04 K2O: 1.0 SiO2: 0.01 Al2O3: 25 H2O: 0.20 R

[0104] Example 11: Synthesis of ZSM-23 zeolite nanosheets at a crystallization temperature of 180℃

[0105] 5.556 g of the quaternary ammonium base R2 solution from Example 2, 1.891 g of water and 0.111 g of aluminum sulfate octadecahydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.08 g of potassium hydroxide was added, followed by 2.5 g of silica sol (40% SiO2) under stirring. After stirring for another 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 180°C for 3 days until complete crystallization. The product was centrifuged, washed and dried to obtain ZSM-23 zeolite nanosheets.

[0106] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0107] 0.04 K2O: 1.0 SiO2: 0.01 Al2O3: 25 H2O: 0.20 R

[0108] Example 12: Synthesis of ZSM-23 zeolite nanosheets under H2O / SiO2=15 conditions

[0109] 3.704 g of the quaternary ammonium base R5 solution from Example 5, 0.743 g of water, and 0.111 g of aluminum sulfate octadecahydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.08 g of potassium hydroxide was added, followed by 2.5 g of silica sol (40% SiO2) under stirring. After stirring for another 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 150 °C for 5 days until complete crystallization. The product was centrifuged, washed, and dried to obtain ZSM-23 zeolite nanosheets.

[0110] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0111] 0.04 K2O: 1.0 SiO2: 0.01 Al2O3: 15 H2O: 0.20 R

[0112] Example 13: Synthesis of ZSM-23 zeolite nanosheets under H2O / SiO2=40 conditions

[0113] 3.704 g of the quaternary ammonium base R5 solution from Example 5, 8.243 g of water, and 0.111 g of aluminum sulfate octadecahydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.08 g of potassium hydroxide was added, followed by 2.5 g of silica sol (40% SiO2) under stirring. After stirring for another 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 150 °C for 5 days until complete crystallization. The product was centrifuged, washed, and dried to obtain ZSM-23 zeolite nanosheets.

[0114] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0115] 0.04 K2O: 1.0 SiO2: 0.01 Al2O3: 40 H2O: 0.20 R

[0116] Example 14: Synthesis of ZSM-23 zeolite nanosheets under K2O / SiO2 = 0.02 conditions

[0117] 4.167 g of the quaternary ammonium base R4 solution from Example 4, 3.280 g of water, and 0.111 g of aluminum sulfate octadecahydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.04 g of potassium hydroxide was added, followed by 2.5 g of silica sol (40% SiO2) under stirring. After stirring for another 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 150 °C for 5 days until complete crystallization. The product was centrifuged, washed, and dried to obtain ZSM-23 zeolite nanosheets.

[0118] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0119] 0.02 K2O: 1.0 SiO2: 0.01 Al2O3: 25 H2O: 0.20 R

[0120] Example 15: Synthesis of ZSM-23 zeolite nanosheets under K2O / SiO2 = 0.08 conditions

[0121] 4.167 g of the quaternary ammonium base R4 solution from Example 4, 3.280 g of water, and 0.111 g of aluminum sulfate octadecahydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.16 g of potassium hydroxide was added, followed by 2.5 g of silica sol (40% SiO2) under stirring. After stirring for another 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 150 °C for 5 days until complete crystallization. The product was centrifuged, washed, and dried to obtain ZSM-23 zeolite nanosheets.

[0122] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0123] 0.08 K2O: 1.0 SiO2: 0.01 Al2O3: 25 H2O: 0.20 R

[0124] Example 16: Synthesis of ZSM-23 zeolite nanosheets under Na2O / SiO2 = 0.02 conditions

[0125] 4.662 g of the quaternary ammonium base R3 solution from Example 3, 2.785 g of water, and 0.111 g of aluminum sulfate octadecahydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.027 g of sodium hydroxide was added, followed by 2.5 g of silica sol (40% SiO2) under stirring. After stirring for another 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 150 °C for 5 days until complete crystallization. The product was centrifuged, washed, and dried to obtain ZSM-23 zeolite nanosheets.

[0126] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0127] 0.02 Na2O: 1.0 SiO2: 0.01 Al2O3: 25 H2O: 0.20 R

[0128] Example 17: Synthesis of ZSM-23 zeolite nanosheets under Na2O / SiO2 = 0.08 conditions

[0129] 4.662 g of the quaternary ammonium base R3 solution from Example 3, 2.785 g of water, and 0.111 g of aluminum sulfate octadecahydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.11 g of sodium hydroxide was added, followed by 2.5 g of silica sol (40% SiO2) under stirring. After stirring for another 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 150 °C for 5 days until complete crystallization. The product was centrifuged, washed, and dried to obtain ZSM-23 zeolite nanosheets.

[0130] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0131] 0.08 Na2O: 1.0 SiO2: 0.01 Al2O3: 25 H2O: 0.20 R

[0132] Example 18: Synthesis of ZSM-23 zeolite nanosheets under SiO2 / Al2O3=50 conditions

[0133] 6.667 g of the quaternary ammonium base R1 solution from Example 1, 0.780 g of water, and 0.222 g of aluminum sulfate octadecahydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.08 g of potassium hydroxide was added, followed by 2.5 g of silica sol (40% SiO2) under stirring. After stirring for another 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 150 °C for 5 days until complete crystallization. The product was centrifuged, washed, and dried to obtain ZSM-23 zeolite nanosheets.

[0134] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0135] 0.04 K2O: 1.0 SiO2: 0.02 Al2O3: 25 H2O: 0.20 R

[0136] Example 19: Synthesis of ZSM-23 zeolite nanosheets under all-silicon conditions

[0137] 4.662 g of the quaternary ammonium base R3 solution from Example 3 and 2.785 g of water were placed in a 25 ml beaker and stirred until clear and transparent. 0.08 g of potassium hydroxide was added, followed by 2.5 g of silica sol (40% SiO2) under stirring. After stirring for 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 150 °C for 5 days until complete crystallization. The product was centrifuged, washed, and dried to obtain ZSM-23 zeolite nanosheets.

[0138] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0139] 0.04 K2O: 1.0 SiO2: 25 H2O: 0.20 R

[0140] Example 20: Synthesis of ZSM-23 zeolite nanosheets using aluminum nitrate nonahydrate as the aluminum source

[0141] 5.556 g of the quaternary ammonium base R2 solution from Example 2, 1.891 g of water, and 0.125 g of aluminum nitrate nonahydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.08 g of potassium hydroxide was added, followed by 2.5 g of silica sol (40% SiO2) under stirring. After stirring for another 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 150 °C for 5 days until complete crystallization. The product was centrifuged, washed, and dried to obtain ZSM-23 zeolite nanosheets.

[0142] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0143] 0.04 K2O: 1.0 SiO2: 0.01 Al2O3: 25 H2O: 0.20 R

[0144] Example 21: Synthesis of ZSM-23 zeolite nanosheets using sodium aluminate as the aluminum source

[0145] 5.556 g of the quaternary ammonium base R2 solution from Example 2, 1.891 g of water and 0.0393 g of sodium aluminate were placed in a 25 ml beaker and stirred until clear and transparent. 0.05 g of sodium hydroxide was added, followed by 2.5 g of silica sol (40% SiO2) under stirring. After stirring for 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 150 °C for 5 days until complete crystallization. The product was centrifuged, washed and dried to obtain ZSM-23 zeolite nanosheets.

[0146] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0147] 0.05 Na2O: 1.0 SiO2: 0.01 Al2O3: 25 H2O: 0.20 R

[0148] Example 22: Synthesis of ZSM-23 zeolite nanosheets using fine silica gel (100% SiO2) as the silicon source

[0149] 4.662 g of the quaternary ammonium base R3 solution from Example 3, 4.285 g of water, and 0.111 g of aluminum sulfate octadecahydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.08 g of potassium hydroxide was added, followed by 1.0 g of fine silica gel (100% SiO2) under stirring. After stirring for 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 150 °C for 5 days until complete crystallization. The product was centrifuged, washed, and dried to obtain ZSM-23 zeolite nanosheets.

[0150] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0151] 0.04 K2O: 1.0 SiO2: 0.01 Al2O3: 25 H2O: 0.20 R

[0152] Example 23: Synthesis of ZSM-23 zeolite nanosheets using silica (100% SiO2) as the silicon source

[0153] 4.167 g of the quaternary ammonium base R4 solution from Example 4, 4.780 g of water, and 0.111 g of aluminum sulfate octadecahydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.08 g of potassium hydroxide was added, followed by 1.0 g of silica (100% SiO2) under stirring. After stirring for 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 150 °C for 5 days until complete crystallization. The product was centrifuged, washed, and dried to obtain ZSM-23 zeolite nanosheets.

[0154] Calculate the amount of each reactant added, and their molar ratio range is as follows:

[0155] 0.04 K2O: 1.0 SiO2: 0.01 Al2O3: 25 H2O: 0.20 R

[0156] Comparative Example 1: Synthesis of ZSM-23 zeolite molecular sieve using N,N-dimethylformamide as an organic template agent

[0157] 0.84 g N,N-dimethylformamide, 8.12 g water and 0.111 g aluminum sulfate octadecylhydrate were placed in a 25 ml beaker and stirred until clear and transparent. 0.43 g sodium hydroxide was added, followed by 3.32 g silica sol (31.5% SiO2) under stirring. After stirring for 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and statically crystallized at 160 °C for 5 days until complete crystallization. The product was filtered, washed and dried to obtain ZSM-23 zeolite molecular sieve.

[0158] X-ray diffraction analysis revealed its structure to be ZSM-23 zeolite molecular sieve. Figure 5 Furthermore, scanning electron microscopy images show that the synthesized product exhibits a conventional rod-like morphology. Figure 6 ).

[0159] Comparative Example 2: Synthesis of ZSM-23 zeolite molecular sieve using pyrrolidine as an organic template agent

[0160] 1.95 g N,N-dimethylformamide, 50.0 g water and 0.41 g aluminum sulfate octadechydrate were placed in a 100 ml beaker and stirred until clear and transparent. 0.35 g sodium hydroxide was added, followed by 3.57 g silica (100% SiO2) under stirring. Then 0.13 g ZSM-23 zeolite molecular sieve seed crystals were added. After stirring for 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and statically crystallized at 180 ℃ for 2 days until complete crystallization. The product was filtered, washed and dried to obtain ZSM-23 zeolite molecular sieve.

[0161] X-ray diffraction analysis revealed its structure to be ZSM-23 zeolite molecular sieve. Figure 7 Furthermore, scanning electron micrographs show that the synthesized product has a large, walnut-like shape. Figure 8 ).

[0162] Comparative Example 3: Using (CH3)3N + CH2CH2CH2N + (CH3)2CH2CH2CH2N + ZSM-23 zeolite molecular sieve was synthesized using (CH3)3 (denoted as Triquat-7) as an organic template agent.

[0163] A solution of 1.04 g Triquat-7 (40%, mass fraction), 13.5 g water, and 0.0393 g sodium aluminate were placed in a 100 ml beaker and stirred until clear and transparent. 0.12 g sodium hydroxide was added, followed by 2.5 g silica sol (40% SiO2) under stirring. Then, 0.10 g ZSM-23 zeolite molecular sieve seed crystals were added. After stirring for 2 hours, the mixed gel was added to a polytetrafluoroethylene stainless steel reactor and dynamically crystallized at 170 ℃ for 6 days until complete crystallization. The product was filtered, washed, and dried to obtain ZSM-23 zeolite molecular sieve.

[0164] X-ray diffraction analysis revealed its structure to be ZSM-23 zeolite molecular sieve. Figure 9 Furthermore, scanning electron microscopy images show that the synthesized product exhibits a conventional rod-like structure. Figure 10 ).

[0165] III. Performance Data and Analysis in Application Examples

[0166] Application Example 1: Performance of ZSM-23 zeolite nanosheets in the hexadecane hydroisomerization reaction

[0167] First, to obtain the hydrogen form of ZSM-23 zeolite molecular sieve, the ZSM-23 zeolite molecular sieve obtained in Example 7 was calcined at 550 °C for 4 h; then, it was placed in a 1 mol / L ammonium chloride solution and exchanged three times at 80 °C for 2-3 h each time. After filtration or centrifugation and drying, it was calcined at 550 °C for 4 h to obtain the hydrogen form of ZSM-23 zeolite molecular sieve. Subsequently, 0.5 wt.% Pt was loaded by equal-volume impregnation to obtain the catalyst Pt / H-ZSM-23 for the hydrogenation reaction.

[0168] Following the procedure of Application Example 1, the zeolite molecular sieves prepared in Examples 8-23 and Comparative Examples 1-3 were subjected to the same treatment to obtain the corresponding catalysts. Then, each catalyst was used for the hydroisomerization reaction of n-hexadecane according to the following method. (1) First, 1 g of catalyst (40-60 mesh) and 1.5 g of quartz sand (40-60 mesh) were weighed and loaded into a tubular reactor. The reactor was then reduced to 400 °C for 2 h at a hydrogen flow rate of 100 ml / min and a heating rate of 2 °C / min. (2) n-Hexadecane was introduced into the reactor at a flow rate of 3 ml / h, a hydrogen flow rate of 30 ml / min, a reaction temperature of 280 °C, and a reaction pressure of 2.0 MPa. Based on the feed conditions and product analysis data, the conversion rate, selectivity, and yield were calculated. The specific results are shown in the table below:

[0169] sample Conversion rate (%) Monoisomeric selectivity (%) Yield (%) Example 7 94.6 80.7 79.8 Example 8 95.4 75.3 74.6 Example 9 94.6 76.2 73.7 Example 10 94.7 72.3 71.2 Example 11 95.1 74.5 73.9 Example 12 93.5 71.9 72.9 Example 13 91.0 80.7 71.2 Example 14 91.3 81.9 75.4 Example 15 91.7 75.6 78.7 Example 16 94.6 73.9 79.8 Example 17 95.4 73.2 78.5 Example 18 95.0 73.4 73.9 Example 19 95.7 67.9 76.9 Example 20 92.2 70.8 74.3 Example 21 92.5 69.2 73.6 Example 22 94.8 67.3 73.4 Example 23 91.9 69.3 72.7 Comparative Example 1 62.4 50.2 65.4 Comparative Example 2 69.8 66.4 61.3 Comparative Example 3 74.5 68.9 67.8

[0170] The data in the table show that, using the zeolite molecular sieves prepared in Examples 7-23 of this invention as catalyst supports, and evaluating the conversion rate, monoisomer selectivity, and yield of n-hexadecane, the results are significantly improved compared to those using Comparative Examples 1-3. Therefore, the above comparison demonstrates that using the nanosheet zeolite molecular sieves prepared in this invention as catalyst supports yields better mass transfer efficiency compared to similar supports with rod-shaped and date-shaped morphologies.

[0171] The above descriptions are merely several embodiments of the present invention and are not intended to limit the present invention in any way. Although the present invention has been disclosed above with preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed structure and technical content to create equivalent embodiments without departing from the scope of the present invention. However, any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for preparing a bisquaternary ammonium base organic template agent, characterized in that, include: (1) Weigh p-dibromobenzyl and 4-pyrrolidinylpyridine in a molar ratio of 1:2 to 5, and then add them to an appropriate amount of acetonitrile; heat and reflux at 50 to 100 °C for 1 to 4 days; (2) After the reaction is complete, add sufficient diethyl ether to the system to form a white solid precipitate; after filtration and drying, obtain bisquaternary ammonium bromide powder; (3) Dissolve an appropriate amount of quaternary ammonium bromide powder in water, and perform exchange treatment with a hydroxide-type anion exchange resin to remove impurity anions and introduce a quantitative amount of OH. - A solution containing a bisquaternary ammonium base organic template agent R was obtained; The molecular structure of the bisquaternary ammonium base organic template agent R is shown in Formula I below: (Formula I).

2. The method according to claim 1, characterized in that, In step (1), the molar ratio of acetonitrile to p-dibromobenzyl is 1:30 to 80.

3. The method according to claim 1, characterized in that, In step (3), the anion exchange resin is added to a bisquaternary ammonium bromide aqueous solution and stirred at room temperature for more than 24 hours; then, 0.1 mol / L hydrochloric acid solution is added to remove OH- ions from the solution. - Quantitative calibration was performed to achieve a concentration of 1–2 mmol / g.

4. The method according to claim 1, characterized in that, The aforementioned hydroxyl-type anion exchange resin is model Amberlite® IRN-78.

5. A method for further synthesizing nanosheet-like ZSM-23 zeolite molecular sieves using the bis-quaternary ammonium base organic template agent as described in any one of claims 1 to 4, characterized in that, Includes the following steps: (1) Weigh the water, silicon source, aluminum source, alkali source and bisquaternary ammonium base organic template agent solution as reaction raw materials, in a molar ratio of 15-40 H2O:SiO2:0-0.02 Al2O3:0.02-0.08 (Na2O or K2O):0.1-0.5 template agent R; mix the raw materials and stir until uniform to obtain a gel-like mixture; (2) Transfer the gel-like mixture to a reaction vessel and allow it to undergo dynamic crystallization reaction at 120–180 °C for 3–7 days; (3) The reaction product was centrifuged, washed and dried to obtain nanosheet ZSM-23 zeolite molecular sieve.

6. The method according to claim 5, characterized in that, The water is deionized water.

7. The method according to claim 5, characterized in that, The silicon source is fine silica gel, white carbon black, or silica sol with a solid content of 40%.

8. The method according to claim 5, characterized in that, The aluminum source is aluminum sulfate octadechydrate, aluminum nitrate nonahydrate, or sodium aluminate.

9. The method according to claim 5, characterized in that, The alkali source is potassium hydroxide or sodium hydroxide.